Pembelajaran Fiqih Berorientasi Capaian Hasil Belajar (Outcome-Based Education) dalam Pendidikan Islam - Febby Erika; Chanifudin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the implementation of Outcome-Based Education (OBE) in fiqh learning within Islamic Religious Education. It employs a qualitative approach using a library research method by analyzing relevant scholarly literature from the past ten years. The findings indicate that OBE provides a systematic framework to reconstruct fiqh learning through the integration of learning outcomes, pedagogical strategies, and assessment. Learning outcomes are formulated to be specific, measurable, and inclusive of cognitive, affective, and psychomotor domains. Student-centered strategies, such as problem-based learning and case studies, are shown to enhance critical and applicative thinking skills. Authentic assessment methods, including portfolios and performance assessments, are more effective in measuring holistic competencies than traditional written tests. However, challenges remain in terms of teachers’ readiness, the validity of affective assessment, and institutional support. This study concludes that the alignment between learning outcomes, strategies, and assessment is essential for effective OBE-based fiqh learning